Kombinasi Pemberian Massage Efflurage dan Olive Oil pada Pasien Tirah Baring di Ruang Intensive Care Unit (ICU) RS PKU Muhammadiyah Yogyakarta - Salsabilla Yasmin Az-Zahra (Pusat Riset dan Inovasi Nasional, 2024)
Abstract: Patients admitted to the Intensive Care Unit (ICU) often develop complications such as pressure sores due to prolonged bed rest. Pressure sores are a major cause of morbidity and mortality in patients. One of the main contributing factors is the lack of supervision and skin care by healthcare workers, leading to damage to skin integrity in the pressure area. This study aimed to determine the effectiveness of a combination of effleurage massage and olive oil in reducing the risk of pressure sores in bedridden patients in the ICU. The method used in this study is a case report. The intervention was carried out for 6 consecutive days, carried out twice in a day, in the morning after oral hygiene and in the afternoon before the morning shift ended. The result of this study show that massage effleurage and olive oil decreased from a score of 8 (high risk) to a score of 12 (moderate risk). Based on the results of research conducted on bedrest patients shows that the combination of efflurage massage and olive oil is effective in reducing the risk of decubitus ulcers in patients.